Explorations in the Stone-Campbell Traditions Essays in Honor of Herman A. Norton - Dunnavant, Anthony L. (Disciples of Christ Historical Society, 1995)
This important collection of essays honors Herman A. Norton (1921-2002), Dean of the Disciples Divinity House at Vanderbilt University from 1951 until his retirement in 1986. Topics from all three branches of the Stone-Campbell Movement are treated including early leaders like Barton Stone and Alexander Campbell, as well as later studies after the Civil War and into the early 1940s.